LINGUISTIC HUMAN RIGHTS AND THE ROLE OF INTERPRETING: THE SLOVENIAN SITUATION - Gorjanc, Vojko; Morel, Alenka (Vertimo studijos, 2017)
To ensure linguistic rights as fundamental rights and the equal treatment of all before the law as well as in other social spheres, translation and interpreting are becoming a necessity; the regulation of this professional area, defined by society’s socially weakest members, is indicative of the level of democracy in a society. The article presents the Slovenian situation from the perspective of the need to ensure community interpreting, taking into account information gained by direct observation and interviews.The Constitution of the Republic of Slovenia generally guarantees linguistic rights in public settings, but their implementation depends on specific laws, thus ensuring and formally regulating interpreting only in court and asylum procedures, while no services are offered in general social and health care settings (except for sign language interpreting), resulting in a power imbalance in interpreter-mediated interactions where interpreting is managed through the improvisation and goodwill of all parties involved. The article ends with plans on how to improve the situation in Slovenia, considering that an integrated arrangement of community interpreting is necessary nowadays, respecting linguistic rights as basic human rights.